2023
DOI: 10.7555/jbr.36.20220125
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an adaptation to hypoxia on cardiac tolerance to ischemia/reperfusion

Abstract: The acute myocardial infarction (AMI) and sudden cardiac death (SCD), both associated with acute cardiac ischemia, are one of the leading causes of adult death in economically developed countries. The development of new approaches for the treatment and prevention of AMI and SCD remains the highest priority for medicine. A study on the cardiovascular effects of chronic hypoxia (CH) may contribute to the development of these methods. Chronic hypoxia exerts both positive and adverse effects. The positive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 220 publications
0
1
0
Order By: Relevance
“…It has been found that remote postconditioning, adaptation to hypoxia, and cold increased cardiac tolerance to I/R [86,141,149]. The question of whether GLP-1 and the GLP1R are involved in the cardioprotective effect of remote postconditioning and adaptation to hypoxia and cold remains to be studied.…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…It has been found that remote postconditioning, adaptation to hypoxia, and cold increased cardiac tolerance to I/R [86,141,149]. The question of whether GLP-1 and the GLP1R are involved in the cardioprotective effect of remote postconditioning and adaptation to hypoxia and cold remains to be studied.…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…Among these illnesses, coronary artery disease (CAD) and acute myocardial infarction (AMI) in particular are the leading causes of morbidity and mortality globally [1,2,3]. One of the potentially fatal coronary-related illnesses closely linked to sudden cardiac death, which affects around three million individuals worldwide each year [4,5], is AMI. The main cause of irreversible myocardial damage in AMI is oxygen deprivation in cardiac cells, which can impair diastolic and systolic function and put the patient at risk for severe and deadly cardiac arrhythmias [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the potentially fatal coronary-related illnesses closely linked to sudden cardiac death, which affects around three million individuals worldwide each year [4,5], is AMI. The main cause of irreversible myocardial damage in AMI is oxygen deprivation in cardiac cells, which can impair diastolic and systolic function and put the patient at risk for severe and deadly cardiac arrhythmias [4,5,6]. Even though AMI can cause several major issues for cardiac function, there are presently limited pharmacological options available for its therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naryzhnaya et al summarized antiarrhythmic, cardioprotective, and vasoprotective effects of chronic hypoxia on enhancing cardiac tolerance to I/R, which involves the complex cellular and molecular mechanisms, such as reactive oxygen species, hormones and humoral factors, kinases, K ATP channels and mitochondria, providing a basis for the new therapeutic approaches in I/R [ 3 ] .…”
mentioning
confidence: 99%